Tendência temporal das comorbidades referidas sobrepeso-diabetes e obesidade-diabetes na população adulta brasileira, 2006 a 2014 - Maíra Barros Louro (2016)
Introduction: The prevalence of excess weight and diabetes mellitus have increased globally and are a public health problem. Excessive weight gain is considered a risk factor for the onset of diabetes mellitus and in this context, the involvement of these simultaneously morbidities can aggravate and accelerate morbidity and mortality and reduce the quality of life of affected individuals. Objective: To determine the temporal trends of prevalence of overweight, obesity and diabetes, as well as the categories of BMI-diabetes, overweight-diabetes and obesity-diabetes. Methods: This is a time series trend study conducted in 26 Brazilian state capitals and the Federal District, using data from the Risk Factor Surveillance System and Protection for Chronic Diseases by Telephone Survey (Vigitel) in 2006-2014, developed with adults (18 years). Sociodemographic datas were used (age, sex, education and marital status), Brazilian regions and capitals. The categories of BMI-diabetes (using BMI categories and presence or absence of diabetes) were created. Simple linear regression technique was employed to verify the occurrence of linear trend of the prevalence of overweight, obesity and diabetes, as well as the categories of BMI-diabetes, and categories overweight-diabetic and obese-diabetic stratified by sociodemographic variables, regions and brazilians capital. Results: The prevalence of overweight, obesity, diabetes and the categories of BMI-diabetes obese-diabetic and overweight-diabetic showed a significant upward trend. Some sociodemographic variables, especially in the age groups 18 to 24 and 25 to 34 years, showed stabilization of prevalence of overweight-diabetic and obese-diabetic. It is noteworthy that the capitals Maceió, Belo Horizonte, São Paulo, Vitória and Porto Alegre had significantly increased prevalence of both overweight-diabetic, as obese-diabetic. Conclusion: This study highlights the originality of monitoring the prevalence of comorbidities, emphasizing the rise in the prevalence of overweight-diabetes and obesity-diabetes in the adult Brazilian population in recent years, showing the usefulness of monitoring systems as a tool in planning and public policy development.